Emblem of faith untouched : a short life of Thomas Cranmer - Williams, Leslie, 1951- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2016)
Thomas Cranmer (1489-1556) was the first Anglican Archbishop of Canterbury, the author of the Book of Common Prayer, and a central figure in the English Protestant Reformation. Few theologians have led such an eventful life: Cranmer helped Henry VIII break with the pope, pressed his vision of the Reformation through the reign of Edward VI, was forced to recant under Queen Mary, and then dramatically withdrew his recantations before being burned alive. This gripping biography by Leslie Winfield Williams narrates Cranmer's life from the beginning, through his education and history with the monarchy, to his ecclesiastical trials and eventual martyrdom. She portrays Cranmer's ongoing struggle to reconcile his two central beliefs -- loyalty to the crown and loyalty to the Reformation faith -- as she tells his fascinating life story.
Beginnings -- Cambridge -- Henry VIII -- Rome -- Reformation -- Archbishop -- Royal supremacy -- Wives -- Doctrine -- Tradition -- Danger -- Conspiracy -- Ordinary time -- Henry's end -- Edward -- Consolidating Reformation -- Mary -- Persecution -- Degradations -- Death -- Appendix A. Key issues in the Reformation -- Appendix B. Reformation eucharistic theology.
Includes bibliography (p. 187-191) and index.
Includes bibliographical references.
Print version record.
Keywords: Cranmer, Thomas, -- 1489-1556.; Cranmer, Thomas, -- 1489-1556.; Great Britain -- History -- Tudors, 1485-1603 -- Biography; Great Britain -- Politics and government -- 1509-1547.; Great Britain -- Church history -- 16th century; Statesmen -- Great Britain -- Biography; Theologians -- England -- Biography; Bishops -- England -- Biography; Bishops; Politics and government; Statesmen; Theologians; England; Great Britain; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christianity / Anglican; Biography; Church history; History; Electronic books